Pengaruh Mekanisme Corporate Governance Terhadap Kinerja Perusahaan Dengan Variabel Mediasi Efisiensi Operasional: Studi Kasus Pada Perusahaan Properti Dan Real Estate di Pt. Bursa Efek Indonesia - Irfan Wihardianto; Mohamad Nur Utomo; Milwan Milwan (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
The aim of this research is to examine the influence of corporate governance mechanisms on company performance. To examine the effect of corporate governance on operational efficiency. To show the influence of operational efficiency on company performance. And to test the operational efficiency mediating variable between corporate governance mechanisms on the performance of property and real estate companies at PT. Indonesian Stock Exchange 2019-2021. This type of research is included in quantitative research. The population for this research is all property and real estate companies registered with PT. Indonesia stock exchange. The sample for this research is property and real estate companies included in the LQ45 Index, namely 6 (six) companies, namely Alam Sutera Realty Tbk (ASRI), Bumi Resources Tbk (BUMI), Lippo Karawaci Tbk (LPKR), Pakuwon Jati Tbk (PWON) , PP Properti Tbk (PPRO), and Summarecon Agung Tbk (SMRA). Data analysis was carried out using path analysis. The research results show that corporate governance (CG) mechanisms have a positive and significant influence on the performance of property and real estate companies included in the LQ45 Index. Corporate governance (CG) mechanisms have a negative and significant influence on the operational efficiency of property and real estate companies included in the LQ45 Index. Operational efficiency has a positive and significant influence on the performance of property and real estate companies included in the LQ45 Index. The operational efficiency variable is a mediating variable between the CG mechanism and the performance of property and real estate companies included in the LQ45 Index.